Strategic reserves in Oregon’s forests for biodiversity, water, and carbon to mitigate and adapt to climate change - Law, Beverly E.; Berner, Logan T.; Mildrexler, David J.; Bloemers, Ralph O.; Ripple, William J. (Frontiers in Forests and Global Change, 2022)
Forest reserves are essential for stemming the loss of biodiversity and contributing to climate mitigation and adaptation. Meeting preservation targets of 30% protection by 2030, and 50% by 2050 would lead to greater protection of animal and tree species habitat, carbon stocks and accumulation, and forests that are important sources of drinking water. Here, we modify our large regional framework to specifically identify at a finer resolution (30m) high priority forestlands for preservation in Oregon, USA by including a resilience metric that represents connectivity and topographic diversity, and identify areas within each ecoregion that are ranked high priority for carbon, biodiversity, resilience and drinking water. Oregon has less than 10% of its forestlands protected at the highest levels, yet its temperate forests are among those with the highest carbon densities in the world. Reserves for surface drinking water sources and forest habitat for birds, mammals, amphibians and reptiles could increase to 50 to 70% protection at the highest levels by 2050. Protected aboveground biomass carbon could triple to 635 teragrams of carbon by 2050. The ownership of the high preservation priority lands for carbon and biodiversity is primarily federal (67% by 2050) followed by private (28% by 2050), with much less in the other ownerships. Forest reserves could be established on federal lands through executive action, regulation and rule-making, while private landowners could be incentivized to store more carbon, limit harvest in certain areas and transfer ownership to land trusts. Protecting mature and old forests on federal lands fulfills an urgent need for protection and provides a low-cost way to simultaneously meet national and international goals. This study provides a flexible, dynamic framework for identifying high priority areas to protect for climate mitigation and adaptation at regional and sub-regional scales.